2021
DOI: 10.3390/su13074037
|View full text |Cite
|
Sign up to set email alerts
|

Research on Indoor Thermal Comfort and Age of Air in Qilou Street Shop under Mechanical Ventilation Scheme: A Case Study of Nanning Traditional Block in Southern China

Abstract: In hot summers, air conditioning (AC) and mechanical ventilation (such as fans) are used as cooling modes that strongly influence the resultant indoor environment, like thermal comfort and air quality in the shops of a Nanning arcade street (qilou). The air circulation mode in shops greatly affects the indoor thermal environment and level of air freshness. The approaches for effectively improving the indoor thermal comfort and air quality are developed in qilou street shops with air-conditioner in a humid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition to the control framework, numerical impacts of several conventional variables such as building geometries and weather conditions were examined by using some computational tools of plug-in modules and co-simulation applications to define real-time interactions between the variables. These methods were used to improve the model's real-time performance responding to the change in outdoor and indoor thermal conditions [17][18][19]. This approach was closely related to the understanding of several types of energy conservation measures, which have been regarded as very difficult to solve due to the unexplained correlation between architectural and mechanical elements.…”
Section: Building Thermal Controlmentioning
confidence: 99%
“…In addition to the control framework, numerical impacts of several conventional variables such as building geometries and weather conditions were examined by using some computational tools of plug-in modules and co-simulation applications to define real-time interactions between the variables. These methods were used to improve the model's real-time performance responding to the change in outdoor and indoor thermal conditions [17][18][19]. This approach was closely related to the understanding of several types of energy conservation measures, which have been regarded as very difficult to solve due to the unexplained correlation between architectural and mechanical elements.…”
Section: Building Thermal Controlmentioning
confidence: 99%
“…However, the statistical weather analysis in terms of building design for warm and humid climates indicated that Malaysia experiences high solar intensity for a long duration, such as the monitoring of heatwave reached (daily maximum temperature 35℃-37℃) was occurred on the northern side of the peninsula [10]. The overheating condition is not as severe as in hot-dry climates, and it is exacerbated by the high humidity and little diurnal temperature change [11]. Moreover, with the acceleration of urbanization of tropical climates in recent years, the building density in traditional urban blocks has become higher in humid and dry areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, situation could be changed with professional concentrations and broad studies [5][6][7] . Some studies considered indoor ventilation taking advantages of nature wind [8] , some focused on ventilation mechanism by using a proper technique [9] , while most concerned on studying relations of spatial variation and nature ventilation for benefiting design in taking water profit is underlined [10][11] . Studies have been done on the use of water body to ease heat effects focusing on water cooling mechanism [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%